L'impact des factures geographiques et environnementaux sur le stade de diagnostic du cancer du sein dans la wilaya de laghouat - LAKEHAL maroua; LEDRA kaouter; LOUCIF sarra (Université Amar Telidji de Laghouat Faculté de Médecine, 2022)
Breast cancer, a major public health issue in Algeria and around the world, representing the leading cancer in women in terms of incidence and mortality. For a long time, several studies have highlighted a number of risk factors involved in the etiology of this cancer, which is still poorly elucidated. The objective of our study is to determine a causal relationship between geographical and environmental factors and late diagnosis of breast cancer in women in Laghouat. For this effect, a multicentre retrospective case-control study was conducted in the following departments: mixed EPH240 beds-Laghouat; EPH Ahmida Benadjila-Laghouat; EPSP of Kasr El Hiran. Covering a period of 04 years from March 2018 to March 2022. During the study period, 124 patients aged between 28 and 78 years with unilateral or bilateral breast cancer were recruited, the average age of occurrence is estimated at 51 years. Effect on the 91 patients who have data on the exact address and TNM stage of cancer, 60 cases were diagnosed at the late stage (65.9%) against 31 cases diagnosed at the early stage (34.1%). Geographic origin which is a main parameter in our study subdivided our population into 71.42% of patients resided in an urban area, and 30 or 28.57% resided in a rural area. Breast cancer is a multifactorial disease. Breast cancer cannot currently be prevented. On the other hand, it can be detected very early as part of regular follow-up with adequate management, to increase the chances of recovery, and improve the prognosis of breast cancer.
90 p.